Improving Badminton Long Serves Through Modifying Learning Media - Nyemas Evi Sumarni; Stephani Yane; Rio Wardhani (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objective. Physical education teachers play a crucial role in promoting successful learning by nurturing critical thinking skills that make the learning process more innovative. However, the lack of adequate facilities and infrastructure poses a significant challenge in achieving successful learning outcomes, particularly in badminton education. To address this issue, this research employs a modified learning media that utilizes recycled materials to enhance the learning outcomes for badminton long serve. Materials and Methods. The study was conducted among fourth-grade students at Madrasah Ibtidaiyah Nurul Islam Ngabang, Landak Regency. Researchers employed a classroom action research method, which included two cycles of data collection and analysis. The study utilized a descriptive research type and employed observation and test techniques for data collection. Data analysis was conducted descriptively and quantitatively based on the results of observations of activities and skills. Result. The study employed two cycles with four meetings each to evaluate the effectiveness of a certain approach. In the first cycle, the participants achieved a final average grade of 79.67 with a 68% completion rate, which was considered unsatisfactory. In the second cycle, the approach was refined and the participants achieved a final average grade of 90.67 with a 92% completion rate, indicating a significant improvement. Conclusion. After conducting extensive research, it has been found that modifying the learning media by utilizing second-hand products can significantly enhance the longevity of badminton services. This study highlights the effectiveness of such an approach in improving the overall performance of badminton players. By employing this technique, players can optimize their skills and achieve a higher level of proficiency in the sport. The findings of this research are valuable and can contribute to the development of new and innovative training methodologies in the field of badminton.